Zjawisko targumizmu w aramejskiej wersji Pierwszej i Drugiej Księgi Kronik - Kuśmirek, Anna (Collectanea Theologica, 2020)
The main objective of the article is to show the features of the Aramaic translation of the First and the Second Books of Chronicles which belongs to the late Targums. The work presents the main data related to the authority, date and origin of the Targum and its manuscripts and the review of major translation techniques and the method of rabbinic interpretation, which are all important elements of the targumism. Linguistic changes, as well as cultural and religious ones, conditioned by various processes that occurred in the community of believers in YHWH over the centuries, were reflected in separate interpretative tendencies.